The Link Between PM2.5 Exposure and Depression: A Systematic Review - Poowaruttanawiwit, Prayuth; Chantim, Chanida; Arunrodpanya, Fasinee; Dedmad, Kanphitcha; Soputaon, Junjilar (Journal of Basic and Applied Pharmacology, 2023)
Objective: This study aimed to investigate the association between exposure to fine particulate matter (PM2.5) and depression by conducting a systematic review. Methods: A comprehensive search of electronic databases was performed to identify relevant studies. The inclusion criteria were limited to original epidemiological studies that examined the association between PM2.5 exposure and depression in human populations. Seven studies met the eligibility criteria and were included in the final analysis. The included studies were conducted in different countries and utilized varying study designs and sample sizes. Systematic review was conducted to synthesize the findings from the individual studies. Results: The results of the systematic review indicated a consistent association between exposure to PM2.5 and depression. Moreover, the studies suggested that this association might be bidirectional, with exposure to PM2.5 leading to depression and depression increasing the risk of PM2.5 exposure. However, the strength of the association varied among studies, indicating that the effect of PM2.5 exposure on depression might be influenced by contextual factors such as population characteristics, geographic location, and exposure duration. More research is needed to establish a causal relationship between PM2.5 exposure and depression. Conclusion: This systematic review highlights the significant impact of PM2.5 air pollution on mental health, particularly its association with depression. Elevated levels of PM2.5 are linked to an increased risk of depression, and long-term exposure to this pollutant raises the risk of depression and anxiety, especially in males. Addressing PM2.5 pollution is crucial for promoting mental well-being.